Does the effect of vitamin A supplements depend on vaccination status? An observational study from Guinea-Bissau - Fisker, Ane B (BMJ Group, 2012)
OBJECTIVE: Vitamin A supplementation (VAS) is estimated to reduce all-cause mortality by 24%. Previous studies indicate that the effect of VAS may vary with vaccination status. The authors evaluated the effect of VAS provided in campaigns on child survival overall and by sex and vaccination status at the time of supplementation. DESIGN: Observational cohort study. SETTING AND PARTICIPANTS: The study was conducted in the urban study area of the Bandim Health Project in Guinea-Bissau. The authors documented participation or non-participation in two national vitamin A campaigns in December 2007 and July 2008 for children between 6 and 35 months of age. Vaccination status was ascertained by inspection of vaccination cards. All children were followed prospectively. OUTCOME MEASURES: Mortality rates for supplemented and non-supplemented children were compared in Cox models providing mortality rate ratios (MRRs). RESULTS: The authors obtained information from 93% of 5567 children in 2007 and 90% of 5799 children in 2008. The VAS coverage was 58% in 2007 and 68% in 2008. Mortality in the supplemented group was 1.5% (44 deaths/2873 person-years) and 1.6% (20 deaths/1260 person-years) in the non-supplemented group (adjusted MRR=0.78 (0.46; 1.34)). The effect was similar in boys and girls. Vaccination cards were seen for 86% in 2007 and 84% in 2008. The effect of VAS in children who had measles vaccine as their last vaccine (2814 children, adjusted MRR=0.34 (0.14; 0.85)) differed from the effect in children who had diphtheria–tetanus–pertussis vaccine as their last vaccine (3680 children, adjusted MRR=1.29 (0.52; 3.22), p=0.04 for interaction). CONCLUSION: The effect of VAS differed by most recent vaccination, being beneficial after measles vaccine but not after diphtheria–tetanus–pertussis vaccine.